Isolation Of Rhizosphere Area Rhizobakteria In Coffee Plants At Several Altitudes In Central Aceh District - Vinny Pratiwi; Zaitun Ritaqwin (Warmadewa University Press, 2025)
Abstract Coffee is cultivated in almost all regions of Indonesia, but the main coffee producing provinces in Indonesia are Aceh, North Sumatra, South Sumatra, Lampung, East Java and South Sulawesi. Sampling was carried out in Pedemun Village, Lut Tawar District and Weh Nareh Village, Pegasing District, Central Aceh Regency. Identification of rhizobacteria was carried out at the Plant Disease Laboratory, Department of Plant Protection, Faculty of Agriculture, Syiah Kuala University, Banda Aceh. implemented from May to July 2023. This research was conducted using qualitative descriptive methods. Sampling was determined by purposive sampling, namely deliberately (without random). The results of the isolation of rhizobacteria in the rhizosphere area of coffee plants resulted in 9 isolates with different codes for each isolate, namely: DP1, DP2, DP3, DP4, PD5, KS1, KS2, KS3, and KS4. Each isolate has different macroscopic characteristics, namely having irregular (irregular) and circular (circular) colony shapes, undulate (wave-like) and entire (flat) colony edges as well as smooth and butyrous (like butter) textures. The staining test results show that all types of isolates include Gram-negative bacteria which are marked in red. All types of isolates obtained had the same cell shape, namely bacilli.